ECONOMIC IMPACT OF VACCINATION WITH PCV13 VS. VACCINATION WITH PCV 10 IN COLOMBIA (2015)
We aim was to estimate the difference of costs and expected cases from serotype coverage of the 13-valent pneumococcal conjugated vaccine (PCV13) and 10-valent pneumococcal conjugated vaccine (PCV10) in the population under 5 years of age in Colombia, using a deterministic model. We considered the probabilities of incidence, mortality and sequelae from infections of pneumonia, meningitis, sepsis and acute otitis media, as well as the clinical effectiveness of PCV13 and PCV10, which were determined by a systematic review of the literature. A2 + 1 immunization schedule was considered, and a 42% herd effect and 84.09% population coverage were assumed. The perspective was the Colombian health system with a time horizon of 5-years. The model showed greater protection of PCV13 in comparison to PCV10. A difference of 98 prevented deaths was observed for meningitis, pneumonia and sepsis. The opportunity cost difference found in the 5-year follow-up between PCV13 and PCV10 vaccines was COP (Colombian pesos) 36,128,082,380 at 2012 prices, which represents COP 7,225,616,476 of difference per year. PCV13 is considered the better alternative, this is mainly due to the impact that this vaccine has on the disease burden of the infections produced by Streptococcus pneumoniae in Colombian children under five years of age.